OPTIMALISASI PROSES PEMBELAJARAN TARI MELALUI PENDISIPLINAN TUBUH PENARI DI SWARGALOKA SCHOOL OF DANCE - Silviana Indah Fihartanti; Romi Nursyam; B. Kristiono Soewardjo (Jurnal Pendidikan Tari, 2024)
The purpose of this study: (1) to find out how important the body discipline method is in Swargaloka School of Dance through Delsarte's Theory. (2) to find out the process of implementing Delsarte's Theory in order to discipline the body in Swargaloka School of Dance. (3) to find out the results of the process of implementing Delsarte's Theory regarding dancing in Swargaloka School of Dance. This study uses descriptive qualitative research because this study cannot be measured numerically. Learning analysis is easier to understand through descriptions with data collected through learning observations, documentation, and interviews. This thesis discusses the optimization of the body discipline process in dance learning in Swargaloka School of Dance. The results of the study show that Swargaloka School of Dance emphasizes good dance techniques, with clear movement flows when dancing. In addition to learning to dance, students at Swargaloka School of Dance also study various other fields of art, such as theater, music, visual arts, make-up and fashion. Dancing is not only about movement, but also related to character, so that speed, tempo, character, flexibility, and body strength become a unity in dance.